2020
DOI: 10.1039/d0sc02686g
|View full text |Cite|
|
Sign up to set email alerts
|

Recent advances in low oxidation state aluminium chemistry

Abstract: Documenting the synthesis and isolation of novel low oxidation state aluminium (Al) compounds, which until recently has seen relatively slow progress over the 30 years since such species were first isolated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 73 publications
1
52
0
Order By: Relevance
“…In addition, the coordination behavior of free one‐coordinate aluminylenes toward transition metals is hitherto unknown [3d,e,j,k, 4a–j, 5d,g, 15, 16] . The formation of 3 – 5 demonstrates the facile access to metal‐aluminylene complexes through this straightforward process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the coordination behavior of free one‐coordinate aluminylenes toward transition metals is hitherto unknown [3d,e,j,k, 4a–j, 5d,g, 15, 16] . The formation of 3 – 5 demonstrates the facile access to metal‐aluminylene complexes through this straightforward process.…”
Section: Resultsmentioning
confidence: 99%
“…These species were formed by a salt metathesis reaction of the corresponding potassium aluminyl compound with a ligand‐stabilized copper halide. It is important to note that the facile synthesis of 8 showcases a new avenue to terminal alumanyl complexes that are extremely rare and otherwise difficult to prepare [4g,j, 12, 13, 36, 37] …”
Section: Resultsmentioning
confidence: 99%
“…PL studies have confirmed the absence of additional defect states in aluminium doped samples, thus ruling out contribution from material defects in volume charge mobilization at the sensor operational temperature (see the ESI †). 46 According to the grain boundary model, [47][48][49][50] chemisorption on metal oxide surface leads to change in grain boundary thickness, affecting electron transport. From the room temperature capacitive studies, it has been observed that for all the samples, decrease in capacitance on exposure to ethanol gas is negligible (see the ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to main group multiple bonds, low oxidation state and/or coordinate main group complexes have also undergone a renaissance in recent years. With several new breakthroughs revealing new classes of compounds, such as nucleophilic aluminyls, [21, 22] as well as advances in bond activations and catalysis [23–28] . The synthesis and bonding nature of main group multiple bonds have been reviewed recently [5, 6, 29–33] .…”
Section: Introductionmentioning
confidence: 99%
“…With several new breakthroughs revealing new classes of compounds, such as nucleophilic aluminyls, [21,22] as well as advances in bond activations and catalysis. [23][24][25][26][27][28] The synthesis and bonding nature of main group mul-tiple bondsh ave been reviewed recently. [5,6,[29][30][31][32][33] Thism inireview,t herefore, focusses on the reactivity of these compounds highlighting the unique transformations that can be achieved due to molecular main group multiple bonds.…”
Section: Introductionmentioning
confidence: 99%